Atheism in Higher Education: A Phenomenological Study of Identity in the Workplace. Issue 1 (2nd January 2018) - Reisner, Carrie
Abstract: Institutions of higher education are perceived to be welcoming to individuals from a variety of backgrounds, including race, ethnicity, sexual orientation, and religion. Is this true for those who identify as atheist as well? This phenomenological study explored how the atheist identity manifests for those who are employed as professional staff in higher education. The participants were employed at public, Midwestern universities in rural communities. Participants who identified with this particular religious minority reported that they were compelled to remain closeted for fear of stigmatization and the risk of discrimination as staff of educational institutions made up of highly Christian communities. The implication for practice is the need to include atheism as a form of religious diversity in order to reduce stigma associated with this identity.